Genetic and epigenetic modifications of F1 offspring’s sperm cells following in utero and lactational combined exposure to nicotine and ethanol - Athareh Pabarja (Nature Portfolio, 2021)
Abstract It is well established that maternal lifestyle during pregnancy and lactation affects the intrauterine programming of F1 offspring. However, despite the co-use of alcohol and nicotine is a common habit, the effects of exposure to both substances on the reproductive system of F1 male offspring and the underlying mechanisms of developmental programming have not been investigated. The present study aimed to examine pre- and postnatal concurrent exposure to these substances on genetic and epigenetic alterations of sperm cells as well as testis properties of F1 offspring compared with exposure to each substance alone. Pregnant dams in the F0 generation randomly received normal saline, nicotine, ethanol, and combinations throughout full gestation and lactation periods. Sperm cells and testes of F1 male offspring were collected at postnatal day 90 for further experiments. High levels of sperm DNA fragmentation were observed in all exposed offspring. Regarding epigenetic alterations, there was a significant increase in the relative transcript abundance of histone deacetylase 1 and 2 in all exposed sperm cells. Moreover, despite a decrease in the expression level of DNA methyltransferase (DNMT) 3A, no marked differences were found in the expression levels of DNMT1 and 3B in any of the exposed sperm cells compared to non-exposed ones. Interestingly, combined exposure had less prominent effects relative to exposure to each substance alone. The changes in the testicular and sperm parameters were compatible with genetic and epigenetic alterations. However, MDA level as an oxidative stress indicator increased in all exposed pups, which may be responsible for such outputs. In conclusion, maternal co-exposure to these substances exhibited epigenotoxicity effects on germline cells of F1 male offspring, although these effects were less marked relative to exposure to each substance alone. These counteracting effects may be explained by cross-tolerance and probably less impairment of the antioxidant defense system.